Do pre-operative abdominal exercises prevent post-operative donor site complications for women undergoing DIEP flap breast reconstruction? A two-centre, prospective randomised controlled trial - Futter, C.M; Weiler-Mithoff, E; Hagen, S; Van de Sijpe, K; Coorevits, P.L; Litherland, J.C; Webster, M.H.C; Hamdi, M; Blondeel, P.N (British journal of plastic surgery, 2003)
The deep inferior epigastric perforator (DIEP) flap is the gold standard for breast reconstruction using abdominal tissue. Unlike the transverse rectus abdominis myocutaneous (TRAM) flap, no rectus abdominis muscle is removed with the flap, but intra-muscular scarring can still cause post-operative complications. Strong abdominal muscles have been advocated as a prerequisite for surgery, but without any evidence as to the potential benefits. This study aimed to investigate the effect of pre-operative abdominal exercises on inpatient pain levels, length of hospital stay, post-operative abdominal muscle strength and function following a DIEP flap. Ninety-three women undergoing delayed breast reconstruction with a DIEP flap between October 1999 and November 2000 were randomly allocated to either a control or exercise group. The exercise group performed pre-operative exercises using the Abdotrim abdominal exerciser. Pre-operatively, outcome measures included trunk muscle strength measured on an isokinetic dynamometer, SF-36, rectus muscle thickness measured using ultrasound, and submaximal fitness. Post-operative pain and length of hospital stay were recorded. Subjects were reassessed using the same outcome measures 1 year post-operatively. There was a statistically significant increase in static (isometric) muscle strength and thickness pre-operatively for the exercise group. One year following surgery, there was a significant decrease in dynamic (concentric and eccentric) flexion strength for both groups, although the clinical significance of this is questionable as the majority of women had returned to pre-operative fitness and the surgery had no impact on functional activities. The static flexion strength of the control group was reduced at 1 year, whereas it was maintained in the exercise group, although this was not statistically significant. One third of women in the control group complained of functional problems or abdominal pain post-operatively compared to one fifth of the exercise group. Overall, the DIEP flap had no major impact on abdominal muscle strength for either group, demonstrating its superiority over the TRAM flap. There was no statistically significant benefit to the exercise group of the pre-operative exercises 1 year following surgery. However, there was a subjective benefit, albeit statistically nonsignificant, in terms of reduced functional problems post-operatively and improved well-being prior to surgery.